2022
DOI: 10.1007/s11414-022-09796-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mental Health Help-Seeking During COVID-19: Social Support, Emotion Regulation, and Mental Health Symptoms

Abstract: Little is known about factors that contribute to mental health help-seeking during disasters beyond attitudes toward counseling. The global pandemic dramatically impacted individuals, families, and communities worldwide. The pandemic led to significant disruptions to family routines, and evidence suggests an increase in instances of mental health symptoms, like depression and anxiety, and poor utilization of mental health services. To better understand psychological factors associated with help-seeking during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Additionally, the lockdowns made it even more difficult for people to access services from mental health professionals (face-to-face) and some psychosocial services were also simply unavailable. Apart from that, studies also showed that seeking professional help during the period of was more common in women, younger people, people with higher education [ 61 ] and those with higher levels of anxiety or depression [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lockdowns made it even more difficult for people to access services from mental health professionals (face-to-face) and some psychosocial services were also simply unavailable. Apart from that, studies also showed that seeking professional help during the period of was more common in women, younger people, people with higher education [ 61 ] and those with higher levels of anxiety or depression [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, persons with higher levels of self-rated anxiety reported higher likelihoods of seeking mental health services while those who did seek help reported higher levels of depression (Tambling et al, 2023). Nascent research has found that persons with disabilities (Wang et al, 2022) and persons who are LGBTQ (Akré et al, 2021) experienced higher rates of depression and anxiety during the COVID-19 pandemic than persons without disabilities, yet there are no studies to date examining mental health disparities experienced by persons with disabilities who are LGBT.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on predictors of requiring and utilizing mental health services during emergency states are relatively scarce. 6 Although psychological health status is the primary determinant, 7 recent findings highlight a decrease in mental health service use even in patients with a previous diagnosis of mental disorders during the pandemic. 8 Thus, additional factors, including sociodemographic characteristics, physical health and COVID-19 history, social relationships, and environmental conditions, may have a role.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Thus, additional factors, including sociodemographic characteristics, physical health and COVID-19 history, social relationships, and environmental conditions, may have a role. 6 Regarding HCWs, exposure to occupational COVID-19 risks and the resulting anxiety and fear may also contribute to the situation. Besides features related to requiring mental health services, some characteristics may also serve as barriers or be altered by needing and/or utilizing mental health services.…”
Section: Introductionmentioning
confidence: 99%